Acting "Straight": Socio-Behavioral Consequences of Anti-Queer Hate Crime Victimization. (29th July 2022) - Kutateladze, Besiki Luka
Abstract: Research on the consequences of hate crime victimization primarily focuses on adverse health and economic effects with limited attention devoted to the socio-behavioral impact of crime. Informed by Intersectionality Theory (Crenshaw, 1989 ) and relying on 400 in-person structured interviews with LGBTQ Latine immigrant victims of crime in Miami, this research finds that 23% of victims had to change housing, 13% began avoiding queer venues/friends, and 35% started acting stereotypically "straight" because of the crime. New immigrant victims were more likely to experience forced relocation due to crime. Victims were more likely to adopt heteronormative behavior/appearance as a result of victimization if they were non-Cuban-American, had higher income, and were more closeted. Findings suggest that coming out can be an important crime control strategy. The paper concludes with a discussion about the benefits and limitations of adopting the intersectionality perspective in quantitative research, and three-stage venue-based sampling used to recruit participants.